On the Relationship Between the Marine Cold Air Outbreak M Parameter and Low‐Level Cloud Heights in the Midlatitudes. Issue 13 (29th June 2020) - Naud, Catherine M.; Booth, James F.; Lamer, Katia; Marchand, Roger; Protat, Alain; McFarquhar, Greg M.
Abstract: Focusing on conditions of subsidence when low clouds are present, ground‐based observations in both the North Atlantic and the Southern Ocean reveal strong relationships between cloud boundary (base and top heights) and different measures of lower tropospheric instability. The difference in potential temperature between the surface and 800 hPa (a metric called M) provides a stronger relationship than measures of inversion strength such as the lower tropospheric stability and estimated inversion strength. This is because (1) inversion strength itself does not correlate well with cloud boundaries, and (2) M contains information that appears important for cloud boundaries. These include the surface forcing through the use of sea surface rather than near‐surface air temperature and an upper level close to the real cloud top. These results expand upon previous work on the importance of M as a predictor of cloud morphology. However, important differences are found in low‐cloud conditions for the North Atlantic as compared to the Southern Ocean (for a given value of M): stronger inversions, deeper boundary layers, and much larger sea level pressures. Therefore, the relationship between cloud boundaries and M differs between the two regions. A general circulation model provides similar relationships as observed between M and both cloud top height and temperature but tends to place clouds higher and at colder temperatures than observed for a given M. This might cause issues with the representation of precipitation, cloud cover and radiation in the Southern Ocean. Key Points: Marine cold air outbreak parameter M correlates better with low‐level cloud boundaries than other stability measures in midlatitudes Differences in large‐scale conditions at Northern and Southern Hemisphere sites explain differences in sensitivities to M A general circulation model reproduces similar relationships, but sensitivities differ causing cooler clouds than observed for a given M